DESAIN SISTEM PEMILIHAN KARYAWAN TERBAIK MENGGUNAKAN AHP PADA LEMBAGA PENYIARAN TVRI - Yudi Wiharto (Jurnal Algoritma, Logika dan Komputasi, 2022)
The concept of a decision support system for selecting the best employees in the Republic of Indonesia Television Public Broadcasting Institution is made based on the problems that exist in that institution that are still doing subjectively and manually and there is no system in it. Where in this selection concept is done by determining the weight value for each attribute, then the ranking process is carried out which will determine the optimal employee performance. Analytic Hierarchy Process (AHP) method was chosen because it can select the best alternative from a number of alternatives. Where by using this method the employee data which is assessed will be compared with other employees with several criteria provisions which will produce the best prospective employees. The results of the study are in the form of a Decision Support System Concept (SPK) concept, which is expected to be able to resolve the selection problem in the best employee assessment and is no longer subjective and the assessment is no longer seen from one aspect based on one perspective.